Kaget, Bingung, Dan Teror: Dimensi Psikokultural Dalam Pengalaman Psikotik - - Subandi (Faculty of Psychology, Universitas Gadjah Mada, 2007)
Psychotic illness is the most severe form of mental illness. Most of psychological and psychiatric literatures focus on the clinical sympstoms. Very few try to understand the phenomenon from the pasient’s subjective perspective. This article aimed at providing an empathic understanding of having psychotic experience. Using ethnographic method, the researcher worked very closely with nine Javanese who experienced psychotic illness for the first time. The psychotic experiences were narrated by the participants themselves and crossed checked with their families. This article discussed the experience of psychosis from the moment of developing psychological and socio-cultural conflicts which was buried inside (the phase of burrying inside), followed by the emerging of psychotic experience (the phase of escaping control). This paper analyzed how Javanese cultural background of the participants were integrated into psychotic experiences. The themes of kaget (being startled), bingung (confused) and teror (terror) will be discussed. Keywords: psychotic illness, ethnographic, Javanese culture